1995
DOI: 10.1042/bj3081025
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and unfolding of the pyruvate dehydrogenase complex by guanidinium chloride

Abstract: The effect of guanidinium chloride (GdnHCl) on the pyruvate dehydrogenase complex (PDC) from bovine heart and its constituent enzymes has been studied. The overall activity of the complex is lost reversibly at low levels of GdnHCl (0.2 M) which cause 40-50% inactivation but no loss of overall secondary or tertiary structures of the individual enzymes; the inactivation of the complex is shown to be caused by dissociation of the E1 and E3 components from the E2/X core assembly. This provides an improved procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The formation of an intermediate trimeric species in the analytical ultracentrifuge has been described [21, 22], but no corresponding peak was observed in the present experiments. Previous fluorimetric studies [23]of the icosahedral bovine heart PDH complex have also suggested that the 60‐mer and trimeric E2p species dissociate into monomers, with 50% loss of tertiary structure at 1.9 M GuHCl and 50% loss of secondary structure at 2.8 M GuHCl.…”
Section: Resultsmentioning
confidence: 89%
“…The formation of an intermediate trimeric species in the analytical ultracentrifuge has been described [21, 22], but no corresponding peak was observed in the present experiments. Previous fluorimetric studies [23]of the icosahedral bovine heart PDH complex have also suggested that the 60‐mer and trimeric E2p species dissociate into monomers, with 50% loss of tertiary structure at 1.9 M GuHCl and 50% loss of secondary structure at 2.8 M GuHCl.…”
Section: Resultsmentioning
confidence: 89%
“…Research has shown that the PDC can be dissassembled in the presence of chaotropic agents such as guanidinium–HCl. 56 We have found that the addition of 1 M urea to CFPS reaction mixtures prior to loading onto the sucrose gradient results in little or no co-purification of the PDC proteins along with assembled VLPs (data not shown).…”
Section: Resultsmentioning
confidence: 90%
“…It is generally recognized that most enzymes will lose their catalytic activity in denaturant solutions (Zhou et al 1993; West et al 1995), but the AK from shrimp exhibited a small increase in specific activity in low‐concentration urea (France and Grossman 1996). Most AKs are 40‐kDa monomers, and the other PKs—CK, GK (glucokinase), and LK—are dimeric, or octameric in the case of mitochondrial CK (Fritz‐Wolf et al 1996).…”
mentioning
confidence: 99%